"H2Ride" Fuel Cell Plug-in Shuttle Bus Demonstration Project at Hawaii Volcanoes National Park and Hydrogen Fueling Demonstration Project on the Big Island of Hawaii. (12th February 2016) - Ewan, Mitch
Abstract : This paper describes the hydrogen infratsructure and hydrogen fuel cell shuttle bus demonstration programs that the Hawaii Natural Energy Instiute is conducting on the Island of Hawaii.